Sifat Antioksidatif Ekstrak Kunir Putih (Curcuma mangga Val.) dengan Pelarut Aseton, Etanol atau Metanol - Pujimulyani, Dwiyati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
A study on the antioxidative properties of white saffron extracted with aceton, ethanol or methanol was undertaken. The purpose of this research is to have a white saffron extract with a high antioxidant activity. White saffron rhizome was peeled, washed, grated, and added within either aceton, ethanol or methanol (white saffron : solvent = 1:3 or 1:4) (W/V) then stirred for 1 hour. The residue was washed with solvent in the same volume. The antioxidant activity of the extract was measured by Ferrythiocyanate (FTC) or Thio Barbituric Acid (TBA) methods. The result showed that the antioxidant activity of white saffron extracted with ethanol was higher than that with methanol, and aceton, respectively. The highest antioxidant activity was obtained from the extract of white saffron extracted with ethanol.